2017
DOI: 10.1155/2017/9281519
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐Targeted Antioxidant SkQ1 Prevents Anesthesia‐Induced Dry Eye Syndrome

Abstract: Dry eye syndrome (DES) is an age-related condition increasingly detected in younger people of risk groups, including patients who underwent ocular surgery or long-term general anesthesia. Being a multifactorial disease, it is characterized by oxidative stress in the cornea and commonly complicated by ocular surface inflammation. Polyetiologic DES is responsive to SkQ1, a mitochondria-targeted antioxidant suppressing age-related changes in the ocular tissues. Here, we demonstrate safety and efficacy of topical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 70 publications
6
45
0
4
Order By: Relevance
“…The total antioxidant activity in AH was analyzed via hemoglobin/H 2 O 2 /luminol system, as described in our previous works [68][69][70]. Briefly, the AH samples were diluted 200-fold with PBS and added to the reaction mixture, containing 0.01 mm luminol and 0.5 mm hemoglobin.…”
Section: Total Antioxidant Activity Analysismentioning
confidence: 99%
“…The total antioxidant activity in AH was analyzed via hemoglobin/H 2 O 2 /luminol system, as described in our previous works [68][69][70]. Briefly, the AH samples were diluted 200-fold with PBS and added to the reaction mixture, containing 0.01 mm luminol and 0.5 mm hemoglobin.…”
Section: Total Antioxidant Activity Analysismentioning
confidence: 99%
“…The pathological changes of mitochondrial-related dysfunctions, including accumulation of ROS and superoxide in the mitochondria and MMP (△Ψm) reduction, were discovered in AMD [25]. In other mitochondrial targeting compounds [10,14,31], we observed that pretreatment with TPP-Niacin signi cantly enhanced the MMP and improved the mitochondrial ultrastructure in a phenotypic analysis by EM, compared to H 2 O 2 alone. Based on these data, we next analyzed the expressions of mitochondria-related genes, such as OXPHOS subunits, mitochondrial dynamics, and mitochondrial DNA replication and transcription genes.…”
Section: Discussionmentioning
confidence: 86%
“…DES affects up to 40% of the adult population and manifests as eye irritation, hyperemia, glare, eye fatigue, and blurred vision [2,3]. Etiologically, alterations in tear homeostasis are associated with dysfunction of the lachrymal and/or Meibomian glands (such as in Sjögren syndrome and Meibomian Gland Dysfunction (MGD)) as well as a number of other factors, including contact lens wearing, adverse effects of various medications, complications of ocular surgery and general anesthesia [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…thereby providing local antioxidant defense [17,18]. Accordingly, the inflammatory component of DES can be attenuated by the topical administration of antioxidants [6,19].…”
Section: Introductionmentioning
confidence: 99%